2008
DOI: 10.1142/s0218810408003918
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Safety and Efficacy of a Pneumatic Finger Tourniquet

Abstract: Finger tourniquets are widely used in hand surgery. However, they do not provide an estimate of the amount of pressure exerted and can potentially be left in situ with grave consequences. We assessed the pneumatic finger tourniquet in 57 adult patients in operations under local anaesthesia distal to the proximal interphalangeal joint. The average tourniquet time was 12 minutes. The tourniquet maintained its pressure for the length of the operation in 96.5% of cases. This airtight flat tubing is made of synthet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…[ 10 14 ] Some previous authors had suggested the use of pneumatic digital tourniquets; however, these are not yet popularly used. [ 15 , 16 ] Instead, most digital tourniquets are non-pneumatic and do not provide the exact value of pressure when applied on digits. Therefore, it is necessary to evaluate whether digital tourniquets are compressing the underlying soft tissue too much or not enough.…”
Section: Introductionmentioning
confidence: 99%
“…[ 10 14 ] Some previous authors had suggested the use of pneumatic digital tourniquets; however, these are not yet popularly used. [ 15 , 16 ] Instead, most digital tourniquets are non-pneumatic and do not provide the exact value of pressure when applied on digits. Therefore, it is necessary to evaluate whether digital tourniquets are compressing the underlying soft tissue too much or not enough.…”
Section: Introductionmentioning
confidence: 99%